Profil kemampuan motorik kasar anak pada Murid Kelas 1 SDN Takkalasi Kabupaten Barru - Hasyim Hasyim; Ishak Bachtiar (Seminar Nasional LP2M UNM, 2019)
The purpose of this study was to determine the level of gross motoric abilities of students. This type of research is quantitative descriptive research with a survey method. The population in this study is all the number of students totaling 20 students and the sample used is class I, amounting to 26 students with sampling techniques with purposive sampling. The technique of collecting data through tests, documentation. The data obtained by researchers were analyzed using statistics with descriptive analysis of percentages. The results of the gross motoric abilities of the children before being given treatment in the form of modification activities of rope jumping games showed that of the 20 number of children, 0% were in the developing category as expected, 90% were in the category of developing, and 10% were in the undeveloped category.